Government's Role in Managing Marine Tourism in Tanjung Bira Bulukumba Regency: Collaborative Governance Perspective - Ahmad Luthfi; I Made Arie Widyasthana Wartana Putra; Ali Roziqin; M Faqih Naufal; Andi Rahmat Hidayat; Ynesita Annabelle Widjaja (Universitas Teuku Umar, 2023)
This study aims to analyze the starting conditions and collaboration between government, private and the community in managing Tanjung Bira marine tourism in Bulukumba Regency. Qualitative approaches are used with descriptive methods. Qualitative data collecting techniques were observation and interviews for primary data and documents for secondary data. In addition, triangulation process had done to reach reliable and valid data. Then, data were analyzed by cross interpreting the interview trancsripts and documents. The results showed that conditions in the government, private and the community already had the conditions to support collaboration in managing Tanjung Bira marine tourism in Bulukumba Regency. The collaboration process between the government, private and community in managing Tanjung Bira marine tourism in Bulukumba Regency has gone through all stages or the process of creating collaboration. This research implied that the absence of a continuous collaborative forum is crucial to build trust, commitment, and shared understanding between the Tanjung Bira’s stakeholders